CHARACTER EDUCATION: CREATORS OF THE NATION - Shirin Kulkarni; Abdul Karim (Universitas Pendidikan Indonesia, 2022)
Until now, there are still many deviant behaviors carried out by students, such as brawls, bullying, drug cases, and other immoral behavior. This behavior when viewed from an Islamic point of view is certainly very contradictory because this behavior is very likely to cause a decrease in quality Human Resources (HR). The existence of national education goals stated in the Law on the National Education System Number 20 of 2003 is one of the efforts that can be made to minimize these deviant behaviors which in turn can also create quality Human Resources (HR). It can be said that the purpose of national education is closely related to character education. The purpose of this study is to determine character education, especially religious values that can create a nation's successor that has a positive impact on the country. The research method used in this study is a qualitative method through literature study or literature review by collecting several reading journals, after that they are reviewed, and analyzed according to research needs. The data collection technique was carried out by collecting data from various systematic search studies. The results obtained from the research are that quality Human Resources (HR) are created not only because of one's intellectuality, but must also pay attention to the spiritual and religious aspects. Therefore, character education related to religious aspects is very important to be realized both in the school environment and in the family environment. The form of its application can be started by habituation to simple things, such as being a good role model for students or children and doing activities related to religious values continuously or continuously.